2020
DOI: 10.1093/jrr/rraa087
|View full text |Cite
|
Sign up to set email alerts
|

Impact on dose distribution and volume changes of a bioabsorbable polyglycolic acid spacer during chemo-proton therapy for a pediatric Ewing sarcoma

Abstract: The clinical utility of a recently developed bioabsorbable polyglycolic acid (PGA) spacer has not yet been established in pediatric patients; therefore, we aimed to investigate its utility during chemo-proton therapy for pediatric cancer. Proton depth–dose curves were obtained in a water phantom with or without the spacer. Computed tomography (CT) scans were performed for the PGA spacer immersed in saline for 2 weeks to measure CT numbers and estimate the relative stopping power (RSP) for the proton beams. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…migration and obstruction) have also been reported [ 11 , 12 ]. Absorbable spacers that have been developed in recent years are designed to maintain their thickness for about two months and then be gradually absorbed, so that dose reduction to surrounding important organs can be maintained during the irradiation period [ 13 , 14 ]. In addition, it has been reported that serious acute and late adverse events do not occur [ 15 ], and absorbable spacers can be used under health insurance for particle therapy in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…migration and obstruction) have also been reported [ 11 , 12 ]. Absorbable spacers that have been developed in recent years are designed to maintain their thickness for about two months and then be gradually absorbed, so that dose reduction to surrounding important organs can be maintained during the irradiation period [ 13 , 14 ]. In addition, it has been reported that serious acute and late adverse events do not occur [ 15 ], and absorbable spacers can be used under health insurance for particle therapy in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Explanation [77,78,[125][126][127] ESFT accounts for 5% of childhood and adolescent tumors. About 25% of primary lesions in soft tissues are ESFTs, with bone tumors accounting for the other 75%.…”
Section: Recommendationmentioning
confidence: 99%
“…In Japan, the use of spacers in particle therapy to the abdominal area is covered by public health insurance, making it part of the standard treatment. Recently, the first case of a pediatric malignant tumour who was treated with PGA spacer and proton therapy was reported with surgical (13) and radiotherapy aspects (14). However, because the number of particle therapy centres is small, limited access restricts its widespread use.…”
mentioning
confidence: 99%